Outcome of surgical decompression in resistant de Quervain tenosynovitis - KC, Bhogendra Bahadur; Lamichhane, Norman; Parajuli, Shiva Prasad; Dhakal, Sabita (Journal of Patan Academy of Health Sciences, 2017)
Introductions: De Quervain tenosynovitis is a common cause of functional impairment. Steroid injection has good result but significant numbers of cases develop resistance requiring surgical decompression. This study assesses the outcome of surgery. Methods: Symptomatic de Quervaint tenosynovitis cases resistant to conservative treatment that underwent surgical decompression and postoperative thumb immobilization using thumb spica splint cast during four and half years were analyzed. They were followed for at least three months for clinical and functional outcome. Patient demography, visual analogue score (VAS) and complications were analyzed descriptively. Results: There were 34 cases of de Quervaint tenosynovitis, mean age 42±16 years, and female 88.2%. Treatment was successful in all cases. The mean VAS score reduced to 0.5 from 6.82, p-value